Strengthening Adolescent Mental Health Through School-Based Preventive Education and Coping Strategies at SMKN 1 Lembah Gumanti - Mahathir, Mahathir; Wenny, Bunga Permata; Banowo, Agus Sri; Yuliharni, Siti; Sumarsih, Gusti; Jamil, Mohd; Yeni, Fitra; Sabri, Rika; Adelirandy, Okky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Adolescence is a critical developmental stage marked by physical, psychological, emotional, and social transitions that increase vulnerability to mental health challenges. Internal and external stressors such as academic pressure, peer relationships, and the school environment can heighten the risk of psychological distress. This community service program was conducted on 28 May 2025 at SMKN 1 Lembah Gumanti, Solok, West Sumatra, through collaboration between the Faculty of Nursing, Universitas Andalas, and the school community. The program aimed to increase awareness of adolescent mental health and promote preventive strategies through school-based education. The intervention was delivered in three phases: (1) screening and problem assessment using the SRQ-29, (2) educational sessions, and (3) stress management workshops. A total of 196 Grade XI students participated. Pre-test and post-test results demonstrated measurable improvements in knowledge of adolescent mental health (Mean pre-test = 7.69, SD = 1.89; Mean post-test = 8.49, SD = 1.91). Students also reported increased awareness of internal (resilience, emotional regulation, mindfulness) and external (peer support, school environment) factors influencing mental health, as well as confidence in applying stress management techniques. These findings underscore the importance of school-based interventions in raising awareness, strengthening coping skills, and preventing mental health problems among adolescents. Future programs may expand by incorporating peer-support models such as student mental health ambassadors to ensure sustainability and long-term impact.